Professionalism in Medical Education: Current Concepts - khalid, Fouzia; Safdar, Maria; Ahmed Noor, Amna; Fatima, Minahil (Journal of Neonatal Surgery, 2025)
Objectives: This review will set out to examine the emerging ideas about professionalism in medical education, its characteristic features, evaluation methods and the issue of professionalism in the modern context of the academic world. The question is to be used to draw focus on the importance of professionalism as a core competency that leads to ethical clinical practice and lifelong learning in medical trainees. Study Design and Setting: Literature published between 2015 and 2025 was used as a basis to conduct a narrative review. PubMed, Scopus, and Google Scholar were searched and articles about professionalism structures, evaluation models, and methodologies of teaching in undergraduate and postgraduate medical schools were found. General medical council (GMC), Accreditation Council for Graduate Medical Education (ACGME) and World Federation for Medical Education (WFME) guidelines that are relevant were examined. Methodology: Peer-reviewed journals, institutional reports, and documents of education policy were synthesized to obtain data. The thematic analysis was used to determine the appearance of professionalism dimensions such as communication, empathy, accountability, and social responsibility. The comparison of trends in different medical curricula in different countries was conducted. Results:Professionalism is now being seen as a multidimensional construct that implies values, behaviors, and identity formation. New models focus on reflective practice, interprofessional cooperation and patient-centered ethics. The concept of assessment has developed away beyond subjective observation to the structured forms of assessment, like professionalism mini-evaluation, reflective portfolios, and multisource feedback. The professional development of the learners depends greatly on faculty development and institutional culture. Conclusions: Medical education and clinical competence have been anchored on professionalism. The incorporation of explicit teaching, unremitting feedback, and modeling on an institutional basis are instrumental in maintaining professional practices. Modern practices promote long-term assessment and mentoring in order to make sure that professionalism is not only imparted but also transferred as a lifelong professional identity..